Efektivitas Cuka Tuak Aren (Arenga pinnata Merr.) sebagai Reagen Alternatif Pemeriksaan Protein Urin - HUSNANINGSIH, ASPARIN; Lalu Srigede; Yudha Anggit Jiwantoro; Ida Bagus Rai Wiadnya (Journal of Indonesia Laboratory Students (JILTS), 2024)
Background: Palm sap (Arenga pinnata Merr.) has an acid content that comes from fermentation in the form of alcohol, then turns into vinegar acid due to an increase in acidity by Acetobecter Acetic bacteria. This vinegar acid has the property of being a weak acid. The vinegar acid content in palm oil can be used as a reagent in urine protein examinations. The principle of urine protein examination is that urine protein is denatured by heating and acid addition. Research Objective: Determine the effectiveness of palm wine vinegar (Arenga pinnata Merr.) as an alternative reagent for urine protein examination. Research Method: This study is quasi-experimental and the sample in this study is protein positive urine with incidental sampling technique. The number of treatments was 3 treatments and replicated 9 times. Research Results: The results of urine protein examination using alternative reagents of palm wine vinegar (Arenga pinnata Merr.) with concentrations of 4%, 6% and 8% have similar results with examinations using 6% acetic acid solution as a control. Conclusion: Palm wine vinegar (Arenga pinnata Merr.) with concentrations of 4%, 6% and 8% is effectively used as an alternative reagent for urine protein examination. Keywords: Palm Vinegar, Urine protein, Acetic acid 6%.